Corporate foreign currency borrowing and investment: The case of Hungary - Marianna Endrész; Péter Harasztosi (Magyar Nemzeti Bank, 2014)
The paper investigates the impact of foreign currency lending in the Hungarian corporate sector on real investment. Using a rich micro dataset we consider two questions. First we test whether foreign currency (FX) lending - by lowering user cost and easing liquidity constraints - contributed to larger investment before the crisis. The second question focuses on balance sheet effects - whether the large domestic currency depreciation observed during the great recession resulted in lower investment rate for firms with foreign currency loans. We try to separate and measure both the competitiveness and balance sheet effect of depreciation. In order to answer these questions several methods are employed - OLS regression, regression enhanced with interaction-terms, and matching. The uniqueness of the paper lies in its almost full coverage in terms of firms and FX exposures, and the richness of the dataset. The results show that before the crisis FX lending increased investment rates. In addition, evidence is found on the liquidity easing channel being effective, i.e. the effect was larger in the case of smaller and non-traded firms. During the crisis the investment rate of firms with FX loans declined more because of balance sheet effects triggered by the depreciation. More liquidity constrained firms suffered more. On the other hand, the evidence on the competitiveness effect is weaker and less robust. Although one would expect that the effect of the exchange rate is non-linear and heterogeneous, the more general non-parametric approach (matching) yields estimates that do not statistically differ from the simple linear regression coefficients.
Keywords: E44; G01; G31; G32; 330; liability dollarization; currency mismatch; investment; balance sheet effects; liquidity constraints